САНХҮҮГИЙН БА УЛС ТӨРИЙН ХЯМРАЛЫН ХАРИЛЦАН ХАМААРЛЫН АСУУДАЛ - С.Базарпүрэв; Г.Туяагэрэл (Politology, 2023)
This paper is an analysis of the simultaneous determination of financial crisis and political crisis and its consequences. It focuses on a small open economy that faces a debt default decision. But this decision is made by a government that has superior information than the public about the social cost of this debt. Citizens can dismiss the government, and overrule it’s wrong decision, at the cost of a political crisis. If there is divergence between the objectives of the government and its people, a political crisis may emerge in equilibrium. For this to be the case, foreign debt must be large enough, and international reserves low. When this political equilibrium is seen as a part of a larger investment problem, there are equilibria in which crisis are "only financial" and equilibria in which both financial and political crisis occur. In some cases, these two kinds of equilibria coexist and, in this sense, a loss of confidence by foreign lenders can exacerbate the likelihood of a political crisis. If so, international intervention in financial markets may ensure financial and political stability at little cost. Товч утга: Санхүү ба улс төрийн хямралыг тодорхойлох мөн тэдгээрийн хоорондын харилцан хамаарал ба үр дагаврыг тодорхойлоход энэхүү судалгааны ажлын зорилго оршиж байгаа болно. Санхүүгийн хямрал гэдэг нь улс орны хэмжээн дэх нийт өрийн хэмжээ ба түүний эргэн төлөлт үүнтэй холбоотойгоор үүсэн гарах сөрөг үр дагавруудын илрэн гарч байгаа нэгэн хэлбэр юм.